Development of a hybrid utility/wind/solar power supply system for energy neutral building - Chooi, Kin Fei (2015)
Renewable energy has a very important role to the world especially when the conventional energy resource are running out. There is a need to develop a system that using the maximum potential of nature resource(wind, sunlight, water flow and etc) convert into electricity, this will resolve the critical issue of demanding for electricity consumption and provide a green city. This report explores one of the possible method to develop a hybrid power system that consists of wind power and solar power system. The purpose of the designed system is to reduce the electricity consumption from the utility and create a green environment for one building. All designed system is based on the Singapore environment factors, like wind speed, power rated, assumptions about the system setting and etc, and it simulated and tested by software PSIM 8.0. The result of the system show that the power generate from Hybrid System has a promising future and it is suitable a limited space for a country like Singapore. Ever this system had been scale down, however, the data collected from the simulator show this system is working as designed and it can be done by using simple component like, Op-Amp, Ac to Dc Convector and etc. The conclusion can also be drawn that the system is well designed system. Following an brief analysis of project result, some recommendations for the future work will also presented.